Sphericity Index and E‐Point‐to‐Septal‐Separation (EPSS) to Diagnose Dilated Cardiomyopathy in Doberman Pinschers. (13th November 2013) - Holler, P.J.; Wess, G.
<x xml:space="preserve">Abstract</x> Background E‐point‐to‐septal‐separation (EPSS) and the sphericity index (SI) are echocardiographic parameters that are recommended in the ESVC‐DCM guidelines. However, SI cutoff values to diagnose dilated cardiomyopathy (DCM) have never been evaluated. Objectives To establish reference ranges, calculate cutoff values, and assess the clinical value of SI and EPSS to diagnose DCM in Doberman Pinschers. Animals One hundred seventy‐nine client‐owned Doberman Pinschers. Methods Three groups were formed in this prospective longitudinal study according to established Holter and echocardiographic criteria using the Simpson method of disk (SMOD): control group (97 dogs), DCM with echocardiographic changes (75 dogs) and "last normal" group (n = 7), which included dogs that developed DCM within 1.5 years, but were still normal at this time point. In a substudy, dogs with early DCM based upon SMOD values above the reference range but still normal M‐Mode measurements were selected, to evaluate if EPSS or SI were abnormal using the established cutoff values. Results ROC‐curve analysis determined <1.65 for the SI (sensitivity 86.8%; specificity 87.6%) and >6.5 mm for EPSS (sensitivity 100%; specificity 99.0%) as optimal cutoff values to diagnose DCM. Both parameters were significantly different between the control group and the DCM group (P < 0.001), but were not abnormal in the "last normal" group. In the substudy, EPSS was abnormal in 13/13 dogs and SI in 2/13 dogs. Conclusions and Clinical Importance E‐point‐to‐septal‐separation is a valuable additional parameter for the diagnosis of DCM, which can enhance diagnostic capabilities of M‐Mode and which performs similar as well as SMOD.